Accelerometer-assessed sedentary behaviour among Chinese rural older adults: Patterns and associations with physical function. Issue 17 (2nd September 2022) - Han, Xiaolei; Wang, Xiaojie; Wang, Chaoqun; Wang, Pin; Han, Xiaodong; Zhao, Mingqing; Han, Qi; Jiang, Ziying; Mao, Ming; Chen, Si; Welmer, Anna-Karin; Launer, Lenore J.; et al.
ABSTRACT: Sedentary behaviour is associated with a range of adverse health conditions. Population-based studies have rarely examined the distribution and associated factors of accelerometer-measured sedentary behaviour patterns in rural-dwelling older adults. This population-based study included 2096 rural-dwelling older adults (age ≥60 years; 59.0% women) derived from baseline participants of the MIND-China Study. Total sedentary time and patterns (e.g., uninterrupted bouts and breaks) were derived from the hip-worn accelerometers for 7 days. Physical function was assessed using the Short Physical Performance Battery test. Data were analysed using general linear models. Overall, participants spent 58.8% of daily waking time in sedentary behaviour, with nearly half of sedentary time being accumulated through sedentary bouts of 30+ minutes. Men spent more total and accumulated sedentary time than women in each sedentary bout duration, while women had more daily 1+ minute sedentary bouts than men (all P < 0.001). Controlling for moderate-to-vigorous physical activity and other confounders, more prolonged sedentary time and fewer breaks were significantly associated with poor physical function, balance, lower limb strength, and walking speed (all P < 0.001). In older adults living in rural communities, prolonged sedentary behaviour and less frequent breaks are associated with poor physical function.